Measurement of the B-s(0) lifetime and study of B-s(0)-(B-s(0))over-bar oscillations using D(s)l events - Abreu, P; Adam, W; Adye, T; Adzic, P; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; Amaldi, U; et al. (2000)
Lifetime and oscillations of B0s mesons have been studied in events with a large transverse momentum lepton and a Ds of opposite electric charge in the same hemisphere, selected from about, 3.6 million hadronic Z0 decays accumulated by DELPHI between 1992 and 1995. The B0s lifetime and the fractional width difference between the two physical B0s states have been found to be: τB0s = (1.42+0.14-0.13(stat.) ± 0.03(syst.)) ps ΔΓB0s/ΓB0s < 0.46 at the 95% C.L. In the latter result it has been assumed that τB0s = τB0d. Using the same sample, a limit on the mass difference between the physical B0s states has been set: ΔmB0s > 7.4 ps-1 at the 95% C.L. with a corresponding sensitivity equal to 8.1 ps-1.